INTERPRETASI KONSUMEN TERHADAP KONTEN BLACK CAMPAIGN DI TIKTOK: STUDI RESEPSI AUDIENS DI KOTA DENPASAR - Ni Ketut Regina Chanda Primasari; Jonathan Jacob Paul Latupeirissa (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
Social media platforms, particularly TikTok, have become primary communication channels and information sources for younger generations in the digital era. However, these platforms also facilitate black campaign practices disseminating false or manipulative information to damage competing brands' reputations. This study examines how consumers in Denpasar City interpret black campaigncontent on TikTok based on their media consumption experiences, while identifying factors such as platform usage intensity, content type preferences, and media literacy levels that shape these interpretations. Employing a descriptive phenomenological qualitative approach, this research purposively selected eight active TikTok users aged 20-21 years in Denpasar. Data were collected through in depth interviews, non participant virtual observation, and digital document analysis, ensuring triangulation for credibility. Findings reveal that consumers perceive black campaigns as deceptive tactics prevalent in beauty and food industries, with interpretations shaped by media experiences that generate cognitive and emotional responses ranging from discomfort to active avoidance behaviors. The study demonstrates that black campaigns produce short-term impacts on consumer attitudes, primarily manifesting as purchase hesitation and skepticism toward implicated brands. Theoretically, this research contributes to reception analysis studies in digital mass communication by demonstrating the active role of audiences in critically interpreting manipulative content. Practically, findings underscore the urgent need to enhance media literacy for cultivating critical awareness of manipulative content and promoting ethical digital marketing practices on TikTok. Keywords: Black Campaign, Consumer Interpretation, media Consumption Experience, TikTok, Digital Mass Communication